اختبار الاستعداد للدفع من أجل الحفاظ على جمالية المناظر الطبيعية باستخدام أسلوب التقييم الافتراضي - تدهور جمالية المناظر الطبيعية في منطقة بانياس، نموذجاً- - خضور رسلان; سلمان ثمر علي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعد إعطاء قيمة للبيئة مهمة صعبة للغاية، فالبيئة سلعة عامة. وبغية تجاوز هذا التحدي، استخدم أسلوب التقييم الافتراضي كتقنية تستند على الاستنباط المباشر لهذه القيم من تفضيلات الأفراد المعلنة. ولأغراض هذا البحث تم اختبار إمكانية استخدام هذه التقنية في قياس الاستعداد للدفع لدى أهالي منطقة بانياس من أجل جمالية المناظر الطبيعية باعتبارها سلعة اقتصادية ذات قيمة. وكنتيجة لهذا البحث أظهر 79.7% استعداداً للدفع من أجل جمالية المناظر الطبيعية، بلغ الوسط الحسابي المثقل لهذا الاستعداد للدفع WTP 192.75 ل.س سنوياً للفرد، ترجمه الأفراد كتقدير شخصي للقيمة النقدية التي يعطيها الأفراد لجمالية المناظر الطبيعية على اعتبارها سلعة اقتصادية علماً أن هذه القيمة تقديرية وافتراضية ولا تشكل القيمة الحقيقية لجمالية المناظر الطبيعية. كما أظهر البحث اختلاف الاستعداد للدفع تبعاً للعمر والجنس والمستوى التعليمي ومستوى الدخل الشهري مع التركيز على أن أغلبية غير الراغبين في الدفع هم من الذكور، والفئات العمرية الأكثر رشداً، ونسبة كبيرة من حملة الإجازة الجامعية الأمر الذي يتناقض والمعرفة الكبيرة التي أظهرها أفراد العينة حول المشكلات البيئية في المنطقة وتأثير هذه المشكلات على نوعية حياتهم وبالتالي رفاهيتهم. Giving a value of the environment is a very hard task: Environment is a public commodity. In order to overcome this challenge, The Contingent Valuation Method(CVM) is used as a technique based on direct elicitation of these values from the stated preferences of individuals. For the purposes of this research, this study has tested the possibility of using this technique to assess the willingness to pay in the region of Banias for saving the aesthetic of the landscape as an economic commodity that have a value through measuring the stated preferences of them. Listen Read phonetically Dictionary - <a href="http://www.google.com/dictionary?source=translation&hl=en&q=%D8%AA%D9%82%D9%8A%D9%8A%D9%85%20%D8%A7%D9%84%D8%A7%D8%B3%D8%AA%D8%B9%D8%AF%D8%A7%D8%AF%20%D9%84%D9%84%D8%AF%D9%81%D8%B9%20%D9%85%D9%86%20%D8%A3%D8%AC%D9%84%20%D8%AD%D9%85%D8%A7%D9%8A%D8%A9%20%D8%A7%D9%84%D9%86%D8%B8%D9%85%20%D8%A7%D9%84%D8%A8%D9%8A%D8%A6%D9%8A%D8%A9%20%D8%A7%D9%84%D8%A8%D8%AD%D8%B1%D9%8A%D8%A9%20%D8%A8%D8%A7%D8%B3%D8%AA%D8%AE%D8%AF%D8%A7%D9%85%20%D8%A3%D8%B3%D9%84%D9%88%D8%A8%20%D8%A7%D9%84%D8%AA%D9%82%D9%8A%D9%8A%D9%85%20%D8%A7%D9%84%D8%A7%D9%81%D8%AA%D8%B1%D8%A7%D8%B6%D9%8A%20%20%20%D8%A7%D9%84%D8%AA%D9%84%D9%88%D8%AB%20%D8%A7%D9%84%D8%B5%D9%86%D8%A7%D8%B9%D9%8A%20%D9%84%D9%84%D9%85%D9%86%D8%B4%D8%A2%D8%AA%20%D8%A7%D9%84%D9%86%D9%81%D8%B7%D9%8A%D8%A9%20%D9%81%D9%8A%20%D9%85%D9%86%D8%B7%D9%82%D8%A9%20%D8%A8%D8%A7%D9%86%D9%8A%D8%A7%D8%B3%20%D9%86%D9%85%D9%88%D8%B0%D8%AC%D8%A7%D9%8B%20%20&langpair=ar|en">View detailed dictionary As a result of this research, 79.7% of the population have shown willingness to pay for the aesthetic of the landscape, with arithmetic mean of willingness to pay WTP was 192.75 s.p annually per capita. Individuals translated this offer as a personal estimate of monetary value given by them to the aesthetic of the landscapes taking into consideration that this value is estimated and does not constitute a default real value for the aesthetic of the landscape. This research has also shown that the willingness to pay is depending on age, sex, educational level and the level of monthly income with a focus on the majority who do not wish to pay are male, and from groups that are more rational, and a large percentage of them have a university degree which is contrary to the great knowledge shown by the members of the sample on the environmental problems in the region and the impact of these problems on the quality of their lives and therefore their well-being.